Adherence to thyroid hormone replacement therapy: a retrospective, claims database analysis. (2nd September 2018) - Hepp, Zsolt; Wyne, Kathleen; Manthena, Shivaji R.; Wang, Siting; Gossain, Ved
Abstract: Objective: The objective of this analysis was to compare adherence at 6 months and 12 months across levothyroxine formulations for patients with hypothyroidism. Methods: This retrospective analysis utilized insurance claims data from a commercially insured population from January 1, 2000 through March 31, 2016. Patients were included if they were diagnosed with hypothyroidism and initiated treatment with generic levothyroxine, Levoxyl, Synthroid, Unithroid, or Tirosint. Patients were excluded if they were younger than age 18, were diagnosed with thyroid cancer, received a prescription for liothyronine, or did not have continuous insurance coverage over the study period. Adherence, defined by the proportion of days covered (PDC) ≥ 80%, was examined using multivariable analyses for both 6 and 12 months post-initiation on therapy Results: The study identified 580, 331 patients who fit the study criteria. At 6 months, 40.3% of patients were found to be non-adherent, while 51.9% were non-adherent at 12 months. Synthroid was associated with significantly higher adherence compared to all other levothyroxine formulations at both 6 and 12 months. Compared to generic levothyroxine, the likelihood of being adherent at 12 months was highest for Synthroid (OR = 1.44; 95% CI = 1.43–1.46), followed by Levoxyl (OR = 1.20 95% CI = 1.17–1.23). Tirosint and Unithroid were associated with significantly lower adherence at 12 months compared to generic levothyroxine (OR = 0.65; 95% CI = 0.57–0.75 and OR = 0.79; 95% CI = 0.71–0.89, respectively). Conclusions: This large, retrospective real-world study demonstrated that adherence to levothyroxine remains a concern among patients with hypothyroidism, and that differences in adherence may exist across levothyroxine formulations.